INVESTIGATING ANXIETY ABOUT TEACHING A FOREIGN LANGUAGE AMONG EFL TEACHERS PURSUING THEIR POSTGRADUATE STUDIES - Gannoun, Hameed; Kunt, Naciye; Deris, Farhana Diana (Universiti Malaysia Sarawak, 2023)
In the discipline of teaching English, scholars and even language teachers have long been interested in foreign language teaching anxiety (FLTA). With the increasing proliferation of English as a foreign language (EFL), there is a lack of comprehensive research on FLTA among EFL teachers. Therefore, the current study examines FLTA among 48 EFL teachers during their postgraduate programme at a public university in Northern Cyprus. The current analysis included the administration of the Teacher Foreign Language Anxiety Scale (TFLAS) and interviews. According to the results, the participants experienced varying degrees of foreign language teaching anxiety, and anxiety levels do not correlate with participants’ gender and teaching. The findings also revealed that fear of making mistakes was the primary factor that could induce language teaching anxiety. This study contributes to the existing body of prior research on FLTA with valuable contextualised data that could help alleviate anxiety levels experienced by EFL teachers. © 2023, Universiti Malaysia Sarawak. All rights reserved.
Keywords: anxiety; English as a foreign language teacher; foreign language anxiety; foreign language teaching anxiety